Phase II clinical study on Low-Intensity-Noise Tinnitus Suppression (LINTS) for Tinnitus treatment - Tziridis, Konstantin; Heep, Lara; Piwonski, Nathalie; Nguyen, Katharina; Kölbl, Nikola; Schilling, Achim; Schulze, Holger (Brain Sciences, 2025)
Background/Objectives: Tinnitus treatment is often based on coping strategies, as, still, no causal treatment is available. Based on our “Erlangen model” of tinnitus development, we treated tinnitus patients with individualized, non-masking low-intensity noise (LIN) to reduce the tinnitus loudness. Methods: A total of 72 adult patients with a tinnitus severity index below IV (tinnitus health questionnaire, THQ), a hearing loss not exceeding 40 dB up to 6 kHz, and without experience in hearing aid (HA) usage were included in this study. Their audiograms, tinnitus parameters, THQ scores, and optimal LIN were determined individually. Patients were double-blinded, assigned to a treatment-only (TO) or placebo-and-treatment (PT) group. The TO patients received treatment for four weeks while the PT patients initially received a placebo (low-intensity white noise) stimulation for two weeks and, hereinafter, treatment for four weeks. Every two weeks, the measurements listed above were repeated. The long-term effects on THQ were assessed four weeks after the end of treatment. The data were analyzed by parametric and nonparametric statistics. Results: We identified a significant decrease in the THQ score already after two (η2 = 0.14) and four weeks of treatment (η2 = 0.43), that was still present four weeks after the end of treatment (η2 = 0.15) in the TO group. Subjective individual patient reports hint at a possible complete suppression of the percept by LINTS. The PT group profited much less, as the initial placebo treatment seemed to counteract the LIN effects. Conclusions: Individually fitted LIN treatment seems to be able to suppress tinnitus, in some cases completely. The optimal fitting of the LIN is crucial for treatment success.